Unveiling Shadows: Tracking Youth Disengagement from the Church [Menyingkap Bayangan: Melacak Penyebab Keterpisahan Kaum Muda dari Gereja] - Samuel Ntsanwisi (Universitas Pelita Harapan, 2024)
This study examines the waning attendance in youth ministry within rural and township areas of South Africa's